Representations of Intercourse in American Literature: Gender, Patiency, and "Fuck" as a Transitive Verb - Jensen, Kim Ebensgaard (Academic Quarter | Akademisk kvarter, 2013)
This article investigates representations of sexual intercourse in American literature expressed via the use of fuck as a transitive verb. Its goal is to identify possible trends in the differentiation between men and women’s roles and power relations in such literary representations. Drawing on theoretical notions from cognitive poetics, the present article assumes that literary representations of intercourse reflect and replicate in readers cultural-cognitive models of intercourse and the roles of, and power relations between, men and women therein. The analysis presented here is quantitative and falls under the rubric of corpus stylistics, and it is based on data from the FICTION component of the Corpus of Historical American English. The analysis measures the preference of male or female passive participants in propositional scenarios denoted by transitive fuck, thus allowing for the identification of large-scale patterns in sexual objectification of men or women in American literature.